2012
DOI: 10.1016/j.jmb.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Binding and Membrane Insertion Compete with Oligomerization of the BclXL Apoptotic Repressor

Abstract: BclXL apoptotic repressor plays a central role in determining the fate of cells to live or die during physiological processes such as embryonic development and tissue homeostasis. Herein, using a myriad of biophysical techniques, we provide evidence that ligand binding and membrane insertion compete with oligomerization of BclXL in solution. Of particular importance is the observation that such oligomerization is driven by the intermolecular binding of its C-terminal transmembrane (TM) domain to the canonical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 81 publications
10
36
0
Order By: Relevance
“…Full-length human BclXL (residues 1-233) was cloned into pET30 bacterial expression vector with an N-terminal His-tag using Novagen LIC technology, expressed in Escherichia coli BL21*(DE3) bacterial strain (Invitrogen) and purified on a Ni-NTA affinity column using standard procedures as described previously [40]. Protein concentration was determined by the fluorescence-based QuantIt assay (Invitrogen) and spectrophotometrically on the basis of an extinction coefficient of 47,440 M −1 cm −1 calculated for the full-length BclXL using the online software ProtParam at ExPasy Server [41].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-length human BclXL (residues 1-233) was cloned into pET30 bacterial expression vector with an N-terminal His-tag using Novagen LIC technology, expressed in Escherichia coli BL21*(DE3) bacterial strain (Invitrogen) and purified on a Ni-NTA affinity column using standard procedures as described previously [40]. Protein concentration was determined by the fluorescence-based QuantIt assay (Invitrogen) and spectrophotometrically on the basis of an extinction coefficient of 47,440 M −1 cm −1 calculated for the full-length BclXL using the online software ProtParam at ExPasy Server [41].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that BclXL displays the propensity to oligomerize in solution and that such oligomerization is driven by the intermolecular binding of its C-terminal TM domain to the canonical hydrophobic groove in a domain-swapped trans-fashion, whereby the TM domain of one monomer occupies the canonical hydrophobic groove within the other monomer and vice versa [40]. We postulated that such oligomerization serves as a regulatory switch to turn the anti-apoptotic action of BclXL “off” in quiescent cells but “on” in response to apoptotic cues.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of BCL-XLΔC with basic pH, heat or detergent has also been shown to induce the formation of a domain-swapped symmetric homodimer, in which helices α6-α8 of one monomer participate in forming the prototypical globular structure of the other 23; 24; 25; 26 . At physiological pH in detergent-free solution, we did not observe dimer formation, even after raising the temperature to 45°C, as evidenced by size exclusion chromatography and the absence of characteristic NMR peak changes associated with conformational reorganization of the α5-α6 hinge.…”
Section: The C-terminus Interacts With the Bh3-binding Groove Of Watementioning
confidence: 99%
“…Compared to their water-soluble states, membrane-bound BCL-XL and BCL-W have been proposed to display diminished affinity for their BH3 ligands due to a loosening of the groove structure in the hydrophobic environment 26; 33; 34 . According to current models, membrane binding by water-soluble BCL-2 proteins induces major conformational changes, while BH3 ligand binding by membrane-integrated BCL-2 proteins causes ulterior structural changes and ligand release 3 .…”
Section: Membrane-integrated Bcl-xl Binds a Bh3 Ligand With High Affimentioning
confidence: 99%
“…For example, details of membrane binding of myristoylated and non-myristoylated ARF1, ADP-ribosylation factor 1 (pdb-id 2K5U), was compared in isotropic bicelles [294]. Spontaneous insertion of the apoptotic repressor BclXL into q = 0.5 DMPC/DHPC bicelles was found to cause a dramatic conformational change that inhibits binding with its BH3 ligand [295]. Isotropic bicelles were used to supply lipid substrate to cobra venom phospholipase A 2 for kinetic assays [296].…”
Section: Magic Touch Added To Studies Of Protein Structurementioning
confidence: 99%